Reference measurements for indirect dark matter searches with p+C collisions at the NA61/SHINE experiment - Michał Naskręt on behalf of the NA61/SHINE Collaboration (SciPost Physics Proceedings, 2023)
NA61/SHINE is a large-acceptance fixed-target experiment located at the CERN SPS, which studies final hadronic states in interactions of various particles and nuclei. It is unique in terms of providing data on a variety of collision systems at different collision energies. This allows for wide deuteron, antiproton and antideuteron production cross-section studies. The latter are currently considered a possible dark matter interaction signal with exceptionally small background. The measurements on carbon targets are important to reduce systematic experimental effects due to experiment-internal antideuteron production, as the most abundant element in the path of an incoming particle for the AMS-02 experiment is carbon. This manuscript will focus on analysis of NA61/SHINE data on p+C thin target collisions in the context of light (anti)nuclei production. A preliminary analysis of experimental data and the particle identification method as well as current deuteron and antideuteron yields will be described.